2014
DOI: 10.1371/journal.pone.0088491
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Organophosphate Pesticides and Neurobehavioral Development of Neonates: A Birth Cohort Study in Shenyang, China

Abstract: BackgroundA large amount of organophosphate pesticides (OPs) are used in agriculture in China every year, contributing to exposure of OPs through dietary consumption among the general population. However, the level of exposure to OPs in China is still uncertain.ObjectiveTo investigate the effect of the exposure to OPs on the neonatal neurodevelopment during pregnancy in Shenyang, China.Methods249 pregnant women enrolled in the Central Hospital Affiliated to Shenyang Medical College from February 2011 to August… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
2
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 50 publications
1
68
2
6
Order By: Relevance
“…The DAP metabolite concentrations measured in our study however, were considerably lower compared to the levels observed in China and Taiwan (Huang et al, 2017; Liu et al, 2016; Zhang et al, 2014). This may be explained by China’s heavy use of OP pesticides in agricultural activities (Wu et al, 2010).…”
Section: Discussioncontrasting
confidence: 94%
“…The DAP metabolite concentrations measured in our study however, were considerably lower compared to the levels observed in China and Taiwan (Huang et al, 2017; Liu et al, 2016; Zhang et al, 2014). This may be explained by China’s heavy use of OP pesticides in agricultural activities (Wu et al, 2010).…”
Section: Discussioncontrasting
confidence: 94%
“…Outside of the U.S., urinary metabolites have been measured in pregnant women from China (Shanghai (Wang et al, 2012); Shenyang (Zhang et al, 2014)), Mexico (Fortenberry et al, 2014), Netherlands (Ye et al, 2009, 2008), and Norway (Ye et al, 2009). Across these studies, urinary concentrations of OP insecticide metabolites varied widely; geometric mean (GM) urinary concentrations of TCPY ranged between 1.8 ng/ml (Mexico) and 3.6 ng/ml (Netherlands), whereas GM urinary concentrations of diethyl and dimethyl phosphates ranged between <LOD (1.0 ng/ml) (Shenyang, China) and 7.1 ng/ml (Shenyang, China) and 0.7 ng/ml (Netherlands) and 17.2 ng/ml (Shanghai, China), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Hal tersebut sesuai hasil penelitian di Shenyang, China yang menyebutkan bahwa paparan pestisida jenis organofosfat selama kehamilan mempunyai hubungan yang kuat dengan dampak buruk perkembangan otak bayi baru lahir (Zhang, 2014).…”
Section: Pendahuluanunclassified